A sandwich-type ELISA for the detection of Listeria monocytogenes using the well-oriented single chain Fv antibody fragment. (September 2017) - Liu, Aiping; Xiong, Qing; Shen, Li; Li, Wenli; Zeng, Zhenghai; Li, Cheng; Liu, Shuliang; Liu, Yuntao; Han, Guoquan
Abstract: Listeria monocytogenes (LM) poses a serious threat to public health. The present study details the development of a sandwich-type enzyme-linked immunosorbent assay (S-ELISA) for the detection of LM using well-oriented single chain Fv antibody fragment (scFv) and a polyclonal antibody. The anti-LM scFv, used as capture antibody, was gene-optimized and expressed with a C-terminal PS-tag in Escherichia coli BL21(DE3) for oriented-immobilization on hydrophilic polystyrene microtiter plates. The anti-LM rabbit polyclonal antibody, used as the detection antibody, was prepared using heat-killed LM cells as an immunogen. The developed S-ELISA showed great specificity to LM and had a detection limit of lg 6.5 CFU/mL, which was better than the control S-ELISA using non-oriented scFv as the capture antibody. When the S-ELISA was applied to pork and pasteurized milk samples spiked with LM, strong responses were observed. In conclusion, the developed S-ELISA shows great potential for the rapid detection of LM. Highlights: An S-ELISA for rapid detection of LM using well-oriented scFv was developed. Compared to random immobilization, well-oriented scFv can improve sensitivity. The detection limit of LM in enrichment cultures was lg 6.5 CFU/mL. The S-ELISA was applicable for LM detection in pork and pasteurized milk.